Current digest of the Soviet press - Joint Committee on Slavic Studies (U.S.); American Council of Learned Societies.; Social Science Research Council (U.S.); American Association for the Advancement of Slavic Studies. (Columbus, Ohio, United States, 1949)
From February 1992 continued by: Current digest of the post-Soviet press, ISSN 1067-7542. Absorbed: Current abstracts of the Soviet press, ISSN 0011-3166.Has supplement: Current abstracts of the Soviet press, 1968-70, ISSN 0011-316.